Pemberdayaan Pengelolaan Sampah Anorganik untuk Pembangunan Ekologis dan Peningkatan Ekonomi Lokal di Desa Trewung Grati Pasuruan - Aziz, Abd.; Hendratama, Handik; Fathurrohman, Amang (Humanist Journal, 2024)
Community empowerment through the management of inorganic waste in Trewung Village, Grati Pasuruan, aims to create sustainable ecological development while improving the local economy. This program involves collaboration between the Supporting Team and the village community to manage plastic waste through sorting, Ecobrick and paving block production, and the development of a medicinal plant garden. This process not only reduces waste volume but also adds economic value through recycled products. The program has provided significant benefits, particularly for housewives, by increasing household income and strengthening the local economy. The results show that community-based waste management can create a cleaner, healthier environment while opening sustainable economic opportunities for the people of Trewung Village.